Sufism and the "Modern" in Islam - Din Wahid (Studia Islamika, 2003)
At a time when the popular imagination outside the Muslim world has been captured by images of Muslim "fundamentalists" terrorising the "West" and when predominantly Muslim countries themselves are under a variety of political pressures to express solidarity with narrowly legalistic lslam, it is timely to reappraise the actual variety of Islamic religiosity active in the lives of ordinary Muslims. Considerable effort is now being made by scholars, governments and private risk assessment agencies, to identify the social spaces occupied by intolerant, exclusivist expressions of Islam deriving from narrowly legalistic understandings of Islam. However, less energy is being directed towards identifying the contemporary modalities of liberal, non-exclusiuist modes of lslamic religiosity.DOI: 10.15408/sdi.v10i3.628